Aspects of the Interactive Approach that Affect Learners’ Achievement in Reading Comprehension in Vihiga County, Kenya: A Focus on Background Knowledge - Anyiendah, Mary Susan; Odundo, Paul A.; Kibui, Agnes (American Journal of Social Sciences and Humanities, 2019)
Learners’ background knowledge is an aspect of the interactive approach instruction, which facilitates reading of comprehension passages. In Vihiga County, learners’ performance in English language examinations is not only lower than that of neighbouring counties, but also poorer in the comprehension reading sections. Few studies have examined the connection between learners’ background knowledge and achievement in reading comprehension in Vihiga County. This study aimed at determining the effect of learners’ background knowledge on their achievement in reading comprehension in the said County. A quasi-experimental design was adopted and primary data sourced from 279 learners and 8 teachers. Multiple linear regression analysis generated a model for the experimental group (Model 1) and another one for the control group (Model 2). In both models, learners’ background knowledge caused a positive effect on the achievement in reading comprehension (Model 1: Beta = 0.412, t = 1.965, p = 0.041; Model 2: Beta = 0.413, t = 1.902, p = 0.059). In both models, the effect was significant, at 95% and 90% confidence levels, respectively; thus, leading to rejection of the null hypothesis for being untrue. Nonetheless, the effect was stronger in the experimental than in the control group, which led to the conclusion that training teachers of English language on how to correctly apply the interactive approach instruction is likely to improve their effectiveness in activating learners’ background knowledge, for better achievement in reading comprehension. The study amplifies the need for: continuous training, instructional resources, innovation and use of alternative resources.